Distinctive features of technical training of football players of leading european clubs - Volokhovich A.A. ,; Shilko V.G. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to conduct a comparative analysis of the main aspects of the technical training of football players from leading European clubs. Methods and structure of the study. In the process of studying and analyzing the training process of two famous European clubs, FC Barcelona and FC Liverpool, the experience of technical training of football players, implemented in the structure of advanced sports technologies, was analyzed. Results and conclusions. The use of advanced sports technologies by European clubs, the structure of which provides for a special section of training work, focused on the constant and targeted improvement of the technical readiness of players, taking into account their individual characteristics, allows, ultimately, to educate outstanding football players who occupy leading positions in European and world football.